A veces llegan cartas... : epistolario de José Luis González - González, José Luis, 1926-1996 (Ciento en boca., 2013)
33 letters exchanged between Puerto Rican writer José Luis González and Carmen Rivera Izcoa from Feburary 1976 to July 1987.